Oral & Maxillofacial surgery is ready for patient-centred eHealth interventions − the outcomes of a scoping review. Issue 6 (June 2019) - van den Bosch, S.C.; van de Voort, N.E.M.; Xi, T.; Kool, R.B.; Bergé, S.J.; Faber, M.J.
Abstract: Within the field of oral and maxillofacial (OMF) surgery, eHealth is expected to be a tool to improve quality of care. The aim of this study is to map the research of patient-centred eHealth interventions within OMF surgery by means of a scoping review. After a systematic literature search, relevant studies on patient-centred eHealth interventions for OMF-surgery patients were selected. The interventions were mapped based on their key components, target population and outcome measures. To gain insight in the research phase of evaluation, the framework of the Medical Research Council (MRC) was used. Forty-one papers were included, comprising 34 unique interventions. Nineteen interventions were designed for head and neck cancer patients, 11 interventions concernd video-teleconsultation. According to the MRC framework, 26 papers fitted into the feasibility and piloting phase of research, 8 into the evaluation phase, 7 were in the development phase. No implementation studies were found. This scoping review can be a starting point for those who are interested in applying and evaluating eHealth in their practice. Since many feasibility and pilot studies were found on similar interventions, a more extensive collaboration with and connecting to each other is recommended to catalyze the implementation of eHealth in daily practice. Profound involvement of patients in developing and evaluating eHealth interventions is essential to achieve true patient-centred OMF surgery.